Muhammad Abduh’s Reformist Thoughts and Their Reception in Indonesian and Malaysian Islamic Reform Movements - Widigdo, Mohammad Syifa Amin; Awang Pawi, Awang Azman (Journal of Al-Tamaddun, 2025)
This study investigates how Islamic reform and renewal ideas introduced by Muhammad Abduh (1849-1905) in Egypt have been transmitted, received, and appropriated in Indonesia and Malaysia. Although some previous studies have been conducted on the transmission of Muhammad Abduh in Southeast Asia, they are mainly historical and lack epistemological analysis. Muhammad Abduh’s ideas and works, which had epistemological roots driving Indonesian and Malaysian reformists to implement reform ideas, were discussed trivially. By closely reading the Theology of Unity (Risālat al-Tauhid) of Muhammad Abduh and examining how his ideas are adopted, appropriated, and impacting reform movements in Indonesia and Malaysia, this study shows that the concept of unity of God, the importance of independent reasoning (ijtihād), and positive outlook toward worldly affairs through good deeds have impacted Islamic reform in Indonesia and Malaysia differently. In Indonesia, reform ideas are taken by civil society organizations (CSOs) that continuously promote reform and renewal through civil society-based activities, means, and institutions. In contrast, in Malaysia, they are handled by religious scholars, political figures, and state officials who employ religious institutions, political means, and state apparatus to implement reform.